Exploring Data in Human Resources Big Data - Adela BARA; Iuliana BOTHA; Anda BELCIU; Bogdan NEDELCU (Database Systems Journal, 2016)
Nowadays, social networks and informatics technologies and infrastructures are constantly developing and affect each other. In this context, the HR recruitment process became complex and many multinational organizations have encountered selection issues. The objective of the paper is to develop a prototype system for assisting the selection of candidates for an intelligent management of human resources. Such a system can be a starting point for the efficient organization of semi-structured and unstructured data on recruitment activities. The article extends the research presented at the 14th International Conference on Informatics in Economy (IE 2015) in the scientific paper "Big Data challenges for human resources management".